Metacommunication in public discourse: A case study of the utterance of 'Stupid Worldwide' by Ahmad Sahroni - Rusli Rusli; Emil Fatra; Amru Siola; Thiara Tri Funny Manguma (Priviet Social Sciences Journal, 2025)
This study aims to analyze how metacommunication works in the case of the worldwide stupid speech controversy by Ahmad Sahroni related to the dissolution of the House of Representatives of the Republic of Indonesia. The remark gained public attention not because of the substance of the message about the danger of dissolving the House of Representatives, but because of the choice of words that were considered rude and inappropriate to be uttered by a state official. This research uses a qualitative approach with a case study method through the analysis of critical discourse on statement texts, media reports, and public interaction on social media. The results show that the metacommunication aspect, especially diction and delivery style, is more dominant in shaping public perception than the substance of political messages. Media framing that highlights the world's stupid diction and virality on social media magnifies the resonance of controversy, making it a digital popular culture phenomenon. This controversy not only impacts Sahroni's personal image but also has implications for the institutional delegitimization of the House of Representatives, further deepening the crisis of public trust. Thus, this study confirms that in political communication in the digital age, legitimacy is not only determined by substantive performance, but also by the way elites choose words and communication styles, as well as how their messages are perceived and reproduced in the media space.